In search of a modern character of a doctor: what examples to learn from the greats? Part I - Yu. V. Rodionova (Кардиоваскулярная терапия и профилактика)
At present, additional courses are increasingly being introduced into the postgraduate medical education program, which contain discussions on the personal qualities of a doctor and the functions of the medical profession. To that end, certain moral and ethical reference points are selected from the biographies of physicians of the "past", which are elevated to an ideal and repeated in every biographical article without proper professional evaluation. There is a mythologization of the image of a doctor among the professional community and the reason for this trend, in part, lies in the false idea that the history of medicine can be written without specialized knowledge and without the tools that historians use when analyzing biographical information.The article provides a general overview of the development of medical knowledge, which was influenced not only by political and economic, but also by religious factors. A specialized approach used by historians in the analysis of biographical information is considered. A different view is offered on the potential of interpreting the image of a doctor, evaluating the activities of physicians of the past and forming examples for doctors of the future that would be in demand in modern professional education.